REVIEW OF SEISMIC REFLECTOR SIGNATURES OF CRUSTAL DEFORMATION IN THE APPALACHIAN-CALEDONIDE OROGEN WITH REFERENCE TO THE SPANISH VARISCIDES AND THE URALIDES - McBride J.H.; Knapp J.H. (My University, 2002)
The availability of thousands of kilometers of deep seismic reflection profiles from the Paleozoic orogenic belts around the North Atlantic Ocean provides an unparalleled opportunity to synthesize the contrasts and similarities of crustal deformation fabrics of compressional orogens. Dominating reflector fabrics are (1) shallow crustal sequences of subhorizontal reflections (décollement levels) that abruptly merge with complex dipping zones (sutures or root zones), (2) broad antiformal reflector patterns, in places underlain by a dipping planar reflector and interpreted as asymmetric folding and shearing in the deep crust, (3) complex, subhorizontal reflectors in the middle to lower crust that can be explained in places as intense ductile shearing related to terrane accretion and continental convergence, and (4) zones of deeply penetrating and mostly planar dipping features, interpreted as reverse-sense brittle faults or ductile shear zones. The structure of reflectors nearer the Moho discontinuity is more complex and variable relative to planar reflectors higher in the crust. Reflectors that curve into the Moho seem to typify orogens where the synorogenic lowermost crust is preserved and imply that the Moho acted as a décollement. In contrast, cases where dipping planar reflectors are abruptly cut off by a flat Moho suggest a postorogenic process that has destroyed and reequilibrated lowermost crustal structure. Other variations between the diverse reflector fabrics can in part be understood (and predicted) in terms of variations between thin- and thick-skinned deformation regimes, which are usually not viewed simultaneously on any one profile or group of profiles. More recently acquired deep seismic profiles from the Spanish Variscides and the Uralides provide examples of convergent belts where most of the full crustal orogenic structure has been preserved intact. These may serve as analogs for less well preserved or evolving orogenic belts.